Makna Ambiguitas Pesan Pemberdayaan Masyarakat (Studi Kasus: Kampanye Sosial “Ketimbang Ngemis” di Media Sosial) - Yusmawati Yusmawati; Restiawan Permana (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
As a tool to create community empowerment, Community of Ketimbang Ngemis invites people to participate in social activities by providing information in the form of messages addressed through their social media accounts. Social campaign activities by Community of Ketimbang Ngemis aim to educate, invite, and awaken the community through information published on social media. However, for example, the speech meaning cannot be released from context. The same speech spoken in different situations has the potential to have different meanings. Therefore, the term of Ketimbang Ngemis raises an ambiguous meaning. If it is analyzed based on denotative meaning, this term has the impression that all elderly and disabled people are always begging. Besides that, it can be seen the use of connotative meaning, the terms contained in the wider community so as not to pity the beggars because begging behavior is lazy behavior, which makes a person become helpless and self-sufficient without any connection with others.